Training Paraeducators to Implement a Group Contingency Protocol: Direct and Collateral Effects - Maggin, Daniel M.; Fallon, Lindsay M.; Sanetti, Lisa M. Hagermoser; Ruberto, Laura M. (Behavioral disorders, 2012)
The present study investigated the effects of an intensive training protocol on levels of paraeducator fidelity to a group contingency intervention used to manage the classroom behavior of students with EBD. A multiple baseline design across classrooms was used to determine whether the training was associated with initial and sustained increases in treatment fidelity. Data were also collected on the effects of paraeducator use of the group contingency program on rates of paraeducator, teacher, and student behavior. Results indicated that the training package was associated with immediate increases in paraeducator fidelity, which were subsequently sustained following the removal of systematic performance feedback on paraeducator adherence to the protocol. The implementation of the group contingency program by paraeducators also led to increases in the rates of interactions between paraeducators and students, increases in the rates of teacher instruction, and decreases in the rates of aggressive behavior by students. Findings of the study are discussed within the context of developing effective training methods for paraeducators working alongside students with EBD.